Themes and values in pre-service teachers’ digital storybooks: A content analysis for elementary English education - Najma Macatanto; Desiery Maghinay; John Dale Pendon; Carla Marie Rubio; Esmeraldo Sarad; Kim Silva (CV Rezki Media, 2026)
Background: Digital storytelling has emerged as an innovative pedagogical approach that promotes meaningful learning experiences and enhances student engagement. Objectives: This study examined the themes and values embedded in digital storybooks created by pre-service teachers and explored their implications for teaching English in elementary education. Methods: Using a qualitative content analysis design, ten digital storybooks were purposively selected based on predetermined inclusion criteria. Data were analyzed through directed content analysis using an adapted thematic analysis framework. Results: Findings revealed nine major themes. The most prominent were exploration-related themes (3 out of 10 storybooks, 30%) and family-sharing themes (3 out of 10 storybooks, 30%), followed by community-oriented themes (2 out of 10 storybooks, 20%). Other themes included parent-child communication and financial responsibility. The digital storybooks also embodied core values such as respect, compassion, humility, responsibility, tolerance, forgiveness, and commitment to the common good. Conclusions: These findings suggest that digital storybooks can serve as effective resources for integrating language development, values education, and socio-emotional learning in elementary English classrooms. The study is limited by its small sample size and context-specific dataset. Further research should include a larger dataset and cross-cultural analysis to strengthen the generalizability of findings.